Pengaruh Faktor Keperilakuan Organisasi Terhadap Kegunaan Sistem Akuntansi Keuangan Daerah Di Kabupaten Klaten - Atmaja, Umar Kusuma; , Dra. Nursiam, M.H., Ak., CA (2016)
This study, entitled "Effects of Organizational Behavioral Factors to Regional Financial Accounting System utilities in Klaten District". This study aims to determine, analyze and obtain empirical evidence about the influence of behavioral factors of the organization's financial accounting system usability area in the district of Klaten in accordance Permendagri 64 2014 Top 59 Amendment Regulation 2007. This study was conducted using a survey method with questionnaires. The study population was all the heads of the finance department at the office of Sub SKPD Klaten district. Data analysis was performed to test the validity and reliability, test classic assumptions and hypothesis testing with multiple linear regression method. This study uses primary data and obtained by distributing questionnaires to 60 respondents. The results showed that the behavioral variables organization (supervisor support, clarity of purpose, training) affects the area of financial accounting system usability. This shows that support for the boss, clarity of purpose and training can affect usability in realizing the area of financial accounting system is better in an agency.